PENGARUH KADAR TIMBAL DALAM DARAH TERHADAP JUMLAH TROMBOSIT PADA1IBU HAMIL DI1DAERAH PANTAI KABUPATEN1BREBES - Zahrotun Hasanah; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Platelet is the smallest part of blood cells. Platelets are produced from fragments of megakaryocyte in the bone marrow. Lead poisoning that can result in increased megakaryocytes. Pregnant women is a very vulnerable group exposed to lead. Pregnant women who are exposed to lead has a very high risk to pass on to their children during pregnancy. The aim of this research is to assess the correlation betwen blood lead levels in pregnant women with a number of platelets. The research design used was observational with cross sectional design. This research was carried out on pregnant women in the coastal areas of Brebes Regency in March 2018. The population in this research is 1734 pregnant with as many as 112 research samples of pregnant women. Data collection using a sheet of environmental observation, interview and examination laboratory. Data analysis using the Spearman Rank correlation test. The result of data analysis showed that there was no significant correlation between blood lead levels and platelet counts (p-value = 0.264). The average blood lead levels in pregnant women of 44.36 μg/dL with a minimum value of 3.6 μg/dL, maximum value of 114.8 μg/dL and the average number of platelets on pregnant women of 298,51/mm3 with a minimum value of 163/mm3 and the maximum value of 681/mm3. The conclusion of this research is there is no correlation between blood lead levels and platelet counts in pregnant women in the coastal areas of Brebes Regency.